The Greek Version of the Minnesota Living with Heart Failure Questionnaire and the European Heart Failure Self-care Behavior Scale - Kalogirou, Fotini; Lamnisos, Demetris; Middleton, Nicos; Lambrinou, Ekaterini (My University, 2012)
The psychometric evaluation of the Greek version of the Minnesota living with heart failure questionnaire (MLHFQ) and the translation/validation of the European heart failure self-care behavior scale (EHFScBS).
Keywords: Heart failure; Minnesota living